Mesoporous Pravastatin Solid Dispersion Granules Incorporable Into Orally Disintegrating Tablets - Song, Hojun; Moon, Cheol; Lee, Beom Jin; Oh, Euichaul (Journal of Pharmaceutical Sciences, 2018)
Herein, we aimed to prepare porous granules of pravastatin and evaluate their applicability to orally disintegrating tablets (ODTs). Pravastatin solid dispersion granules (PSDGs-A) were prepared by dispersing pravastatin sodium in D-mannitol (the dispersion medium) in the presence of ammonium bicarbonate (the sublimation agent) using a spray-drying process. The PSDGs-A were round, irregularly shaped, mesoporous agglomerates with appropriate particle size, bulk density, and flowability for the tableting process. The mesopore formation in PSDGs-A resulted from the complete sublimation of ammonium bicarbonate during spray-drying and resulted in a notably high surface area. When the PSDGs-A were blended with ODT excipients and then directly compressed into ODTs (PSDGs-A-ODTs), they were readily incorporated into ODTs without tableting problems and had desirable ODT characteristics. They demonstrated rapid disintegration times because of the fast water uptake of mesoporous PSDGs-A caused by their high surface area. This rapid disintegration of PSDGs-A-ODTs was reflected also by their quick initial dissolution. The mesoporous PSDGs-A prepared with ammonium bicarbonate using the spray-drying process can be used to develop pravastatin ODTs. This spray-dried, mannitol-based solid dispersion of drugs using sublimation solids is a potential formulation technology for ODT product development.
Keywords: Administration, Oral; Anticholesteremic Agents; Bicarbonates; Desiccation; Drug Compounding; Excipients; Mannitol; Porosity; Pravastatin; Solubility; Tablets; Water; formulation; oral drug delivery; physical characterization; solid dispersion; spray-drying; surface chemistry